RofPN - Abordagem para reutilização de processos de negócio - Maracci, Francisco Virginio (2010)
Business processes (BP) and Web Services (SW) are solutions to an inter-organizational communication organized and supported by the establishment of a mutual agreement (electronic contract). The establishment of contracts for electronic business processes in a given area involves a set of common points and differences (variability). Therefore, this thesis proposes an approach to reuse of business processes through the establishment of an effective product line with representation of variability by the UML activity diagram. The proposed approach is applied at the time of hire the BP and SW, not the time of their development. The objective of the approach and the representation is the development of a product line infrastructure for business processes in order to improve the structuring of business processes and Web services and thus enable their reuse. The proposed approach is divided into two life cycles. The life cycle called business processes domain engineering is responsible for defining the domain of BP and the development and publication of the BP and SW. BP Engineering is responsible for setting and product development. The completion of the work took place by applying the approach in the field of telecommunications carriers in order to demonstrate the applicability of the same. The approach demonstrated the advantage of being useful for the structuring of business processes, web services and terms of QoS, thus allowing for the reuse of them.